2017
DOI: 10.18632/oncotarget.14874
|View full text |Cite
|
Sign up to set email alerts
|

VEGF promotes cartilage angiogenesis by phospho-ERK1/2 activation of Dll4 signaling in temporomandibular joint osteoarthritis caused by chronic sleep disturbance in Wistar rats

Abstract: Chronic sleep disturbance (CSD) has been linked to the development of temporomandibular joint osteoarthritis (TMJ-OA). While the pathogenesis of TMJ-OA is unclear, recent studies indicate that osteochondral angiogenesis is important. We developed a rat model of CSD induced TMJ-OA to investigate the changes caused by sleep disturbance and to correlate them with vascular invasion in the TMJ. We found pathological alterations and an increased microvessel density in the rat TMJ following CSD. VEGF, Dll4 and p-ERK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…It is worth noting that there is a significant positive correlation between VEGF and miR-21-5p in vitro. Moreover, according to many studies, miR-21-5p can regulate the phosphorylation of ERK-MAPK signalling pathway components by targeting Spry1 in a variety of cells [15,34,38,39] and based on the close correlation between VEGF and the ERK-MAPK signalling pathway [7,27,38], we speculate that miR-21-5p can promote angiogenesis in TMJ, and this effect is likely related to the degree of phosphorylation of ERK-MAPK signalling pathway components. Finally, the experimental results of the chicken embryo angiogenesis assay and Western blotting showed that miR-21-5p has a pro-angiogenic effect, which was significantly mediated by the ERK-MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is worth noting that there is a significant positive correlation between VEGF and miR-21-5p in vitro. Moreover, according to many studies, miR-21-5p can regulate the phosphorylation of ERK-MAPK signalling pathway components by targeting Spry1 in a variety of cells [15,34,38,39] and based on the close correlation between VEGF and the ERK-MAPK signalling pathway [7,27,38], we speculate that miR-21-5p can promote angiogenesis in TMJ, and this effect is likely related to the degree of phosphorylation of ERK-MAPK signalling pathway components. Finally, the experimental results of the chicken embryo angiogenesis assay and Western blotting showed that miR-21-5p has a pro-angiogenic effect, which was significantly mediated by the ERK-MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 76%
“…It has been confirmed that when VEGF is combined with its signal receptor VEGF2, downstream kinases such as MAPK can be phosphorylated to activate the ERK-MAPK signalling pathway [26]. Moreover, ERK-MAPK signalling pathway activated by VEGF can induce the activation of MMPs [27]. Because VEGF, MMPs and the ERK-MAPK pathways are closely related to the development of OA and there is a close relationship between MicroRNAs determine cell fate by participating in the regulation of extracellular signalling pathways and expression of certain molecules [28], and miR-21-5p has been reported to play an important role in cell apoptosis, pathological growth and stress [29,30], processes that are closely related to OA cartilage lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Blood vessels not only transport oxygen and nutrients throughout the human body but also nourish tumors and other disease conditions [ 2 ]. To date, the precise mechanisms of angiogenesis remain to be defined but a large number of studies have shown that mechanical and chemical stimulation could regulate expression of different cytokine and growth factors to promote endothelial cell proliferation, while angiogenesis is also the key process in cancer development and progression [ 3 ]. Malignant cells are rapidly dividing cells and grow uncontrollably due to activation of oncogenes and/or inactivation of tumor suppressor genes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…They furtherly indicated that the VEGF binds to its receptor (VEGFR-2), leading to extracellular signal-regulated kinase (ERK1/2) activation. The ERK activation, helped the induction of matrix metalloproteinase (MMP), which aid in the degradation of the extracellular matrix during both the initiation and progression of TMJOA [23]. These previously reported mechanisms concerning the implement of VEGF in the pathogenesis of OA, could elucidate the significance of elevated VEGF expression in the chondrocytes of osteoarthritic mandibular condyle in the present investigation.…”
Section: Discussionmentioning
confidence: 57%